Current Value Depreciation: A Conceptual Clarification. - Wolk, Harry I. (The Accounting Review, 1970)
The article clarifies the complexities of the conceptual differences in the methods used to define or measure current value depreciation. Since depreciation is but one aspect in the total problem of income measurement, a brief examination of the purposes or uses of periodic income should be beneficial. The authors, within the confines of the purposes of income, attempt to clarify the concept of depreciation. Finally, given certain information about present prices and changes which have occurred in the structure of prices, a conceptual method for determining depreciation and other related factors affecting asset value changes will be illustrated. Income must be defined before it can be appropriately measured. Therefore, any definition of income must be based upon the intended usage of information generated. The user cost approach, while fundamentally different from replacement-value accounting, must be consistent with some measure of capital maintenance. Dependence upon subjective measurements such as present value of discounted services or estimated minimum cost per unit of output applicable to technologically improved assets is avoided.